Microbiome and pathobiome analyses reveal changes in community structure by foliar pathogen infection in rice - Dastogeer, Khondoker M. G.; Yasuda, Michiko; Okazaki, Shin (Frontiers in Microbiology, 2022)
Increasingly, evidence suggests that the plant rhizosphere may recruit beneficial microbes to suppress soil-borne pathogens, but microbiome assembly due to foliar pathogen infection and ecological mechanisms that govern microbiome assembly and functions in the diseased host are not fully understood. To provide a comprehensive view of the rice-associated microbiome, we compared bacterial and fungal communities of healthy rice and those infected with Magnaporthe oryzae, the causal agent of blast disease. We found that the soil had a greater diversity of bacterial and fungal communities than plant endospheric communities. There was no significant dysbiosis of bacterial and fungal microbiome diversity due to disease, but it caused a substantial alteration of bacterial community structure in the root and rhizosphere compartments. Pathobiome analysis showed that the microbiome community structure of leaf and grain tissues was changed markedly at the pathogen infection site, although the alpha diversity did not change. Correspondingly, the relative abundances of some bacteria and fungi were clearly altered in symptomatic tissues. We noted an increase in Rhizobium bacteria and a decline of Tylospora, Clohesyomyces, and Penicillium fungi in the symptomatic leaf and grain tissues from both locations. According to the inferred microbial network, several direct interactions between M. oryzae and other microbes were identified. The majority of edges in the interaction network were positive in diseased samples, contrastingly, the number of edges was much lower in the healthy samples. With source tracking analysis, we observed a sharp contrast in the source of root endosphere bacteria due to Magnaporthe infection. Whereas the majority (71%) of healthy root bacteria could be tracked from the soil, only a very small portion (17%) could be tracked from soil for diseased samples. These results advanced our understanding and provided potential ideas and a theoretical basis for studying pathobiome and exploiting the microbiome for sustainable agriculture.